SISTEM INFORMASI KEPEGAWAIAN SEBAGAI PENYEDIA INFORMASI PEMILIHAN PEGAWAI PENERIMA PENGHARGAAN SATYA LENCANA KARYA SATYA DI RADIO REPUBLIK INDOSESIA PALANGKA RAYA - Enny Dwi Oktaviyani; Licantik Licantik; Loure Florentina (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2019)
Staffing information system (Simpeg) as an information provider of election Officers Work Medal Awardees Satya Lencana In RRI Palangkaraya aims to be a place of useful information provider for submission of award Satya lencana karya satya so that it could be effective, efficient, and accurate by simplifying the existing system. By having this website is expected to handle the process of logging employees so that it can help in the process of registration of a Nobel Prize Medal work of satya. Methodology in the making of this website using the method waterfall, waterfall method which consists of several parts or stages – stages, namely analysis, design, coding and testing. This methodology was chosen because every step of the development of this website is structured, and clearly documented. The programming language used is PHP and MySQL as a database. At this stage of testing this website using black box testing. Black-Box Testing to focus on the functional specifications of the program. After doing the testing, can be seen the result of this site that this website can perform its function, namely to manage data, time data family history, history of education, employment, lencan setya, data filing SKP, and PKP